Percutaneous Inserted Venous Catheter via Femoral Vein in Extremely Low-Birth-Weight Infants: A Single-Center Experience - Bergón-Sendín, Elena; Soriano-Ramos, María; Méndez-Marín, María Dolores; De Miguel-Moya, Mónica; Fontiveros-Escalona, Diego; Diezma-Godino, Mercedes; Pallás-Alonso, Carmen Rosa; Moral-Pumarega, María Teresa (American Journal of Perinatology, 2019)
Objective This study aimed to assess the applicability of the insertion of small diameter catheters through the femoral vein in extremely low-birth-weight (ELBW) infants.Study Design All femoral small diameter catheters (Silastic or femoral arterial catheter [FAC]) inserted in ELBW infants in a tertiary level neonatal intensive care unit were retrospectively reviewed. Success rate, dwelling time, and percutaneously inserted central venous catheter–related complications were recorded.Results Thirteen small diameter catheters were inserted in seven ELBW infants. Mean gestational age at birth was 25+3 weeks (standard deviation [SD] ± 2.12) and mean birth weight was 686 g (SD ± 204.9). Mean weight at the first time of insertion was 1,044 g (SD ± 376.3). In two occasions, a FAC was used instead of a Silastic. In most cases (11/13, 84.6%), the patient was intubated prior to the procedure. The mean dwelling time was 16.7 days (SD ± 9.8). Most of the inserted small diameter catheters were removed electively (8/12, 66.7%), except for one episode of clinical sepsis from coagulase-negative Staphylococcus and three cases of accidental line extravasation. No other complications were reported. The success rate was 92.3%.Conclusion Femoral venous catheterization using small diameter catheters in ELBW infants may be promising when other routes have been exhausted. Our results support that it is a feasible technique that can be performed at the bedside with successful results when conducted by experienced personnel.
Keywords: central venous catheters; intravenous catheterization; extremely premature infant; neonatal intensive care; catheter-related